2018
DOI: 10.1021/acs.inorgchem.8b02195
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Negative Thermal Expansion by Mechanical Pulverizing in Hexagonal Mn0.965Co1.035Ge Compounds

Abstract: Negative thermal expansion (NTE) material as a compensator is very important for accurately controlling the thermal expansion of materials. Along with the magnitude of the coefficient of thermal expansion, the operating temperature window of the NTE materials is also a major concern. However, only a few of the NTE materials possess both a large operating temperature range and a large thermal expansion coefficient. To explore this type of new NTE material, the Mn 0.965 Co 1.035 Ge fine powders were prepared by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…4,18,19 From the view of structure, M′ atoms at 2d sites (1/3, 2/3, 3/4)/(2/3, 1/3, 1/4) and X atoms at 2c sites (1/3, 2/3, 1/4)/(2/3, 1/3, 3/4) alternately constitute a layered honeycomb structure, and Mn atoms at 2a sites (0, 0, 0)/(0, 0, 1/2) are located in the interlayer to connect M′−X layers. 4,10,16 In this way, the M′−X rings sustain the stability of structure for M′MnX crystal. 20 However, the magnetic moment is mainly contributed by Mn atoms and the shortest Mn−Mn distance along the c axis plays a dominant role in determining the magnetic states.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…4,18,19 From the view of structure, M′ atoms at 2d sites (1/3, 2/3, 3/4)/(2/3, 1/3, 1/4) and X atoms at 2c sites (1/3, 2/3, 1/4)/(2/3, 1/3, 3/4) alternately constitute a layered honeycomb structure, and Mn atoms at 2a sites (0, 0, 0)/(0, 0, 1/2) are located in the interlayer to connect M′−X layers. 4,10,16 In this way, the M′−X rings sustain the stability of structure for M′MnX crystal. 20 However, the magnetic moment is mainly contributed by Mn atoms and the shortest Mn−Mn distance along the c axis plays a dominant role in determining the magnetic states.…”
mentioning
confidence: 89%
“…M ′Mn X ( M ′ refers to transition metal; X = Si, Ge, Sn, etc.) magnets have drawn lots of attention because of their unique structural, magnetic, and electronic features, which give rise to plentiful physical phenomena, including the solid-state caloric effect, , magnetoresistance (MR), the magnetostrictive effect, , negative thermal expansion, , exchange bias, the Hall effect, and magnetic biskyrmions. ,, From the view of structure, M ′ atoms at 2 d sites (1/3, 2/3, 3/4)/(2/3, 1/3, 1/4) and X atoms at 2 c sites (1/3, 2/3, 1/4)/(2/3, 1/3, 3/4) alternately constitute a layered honeycomb structure, and Mn atoms at 2 a sites (0, 0, 0)/(0, 0, 1/2) are located in the interlayer to connect M ′– X layers. ,, In this way, the M ′– X rings sustain the stability of structure for M ′Mn X crystal . However, the magnetic moment is mainly contributed by Mn atoms and the shortest Mn–Mn distance along the c axis plays a dominant role in determining the magnetic states .…”
mentioning
confidence: 99%
“…The samples were annealed at 850 °C for 7 days and then quenched into ice water. In order to reduce the potential effects of internal stress, , powder samples were obtained by grinding the ingot (mortar and pestle) for a relatively short time of 5 min.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Recently, MnCoGe-based compounds were considered as a group of promising NTE materials with giant contraction of the unit cell volume over a reverse martensitic transformation. It is reported that, with indium doping, the unit cell volume could contract by an amount as large as Δ V / V ≈ 3.9% . In MnCoGe-based compounds, there are two stable phasesa low-temperature martensitic phase with the TiNiSi-type orthorhombic structure ( Pnma ) and a high-temperature austenite with the Ni 2 In-type hexagonal structure ( P 6 3 / mmc ) .…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Such magnetovolume effects are mainly triggered by magnetic moment of rare earths (Re) or Mn/Fe/Co atoms [22,23] which however have high reactivity under harsh environments. [9,24,25] As a consequence, most newly reported ZTE alloys show an undesirable environmental instability, e.g., La(Fe, Si, A) 13 , [26] Re 2 (Fe, A) 17 , [27] and (Mn, A)(Co, A)Ge [28] (Re: rare-earth metals, A: transition metals). However, some metals are prone to oxidation to form stable oxide films, like Al 2 O 3 , ZrO 2 , etc., which are resistant to harsh environmental erosion.…”
Section: Introductionmentioning
confidence: 99%